Effect of Telitacicept on Circulating Gd-IgA1 and IgA-Containing Immune Complexes in IgA Nephropathy - Jincan Zan; Lijun Liu; Guisen Li; Hongguang Zheng; Nan Chen; Caili Wang; Deqiong Xie; Li Zuo; Rongshan Li; Pengfei Zhang; Yue Wang; Wenxiang Wang; et al. (Kidney International Reports)
Introduction: Telitacicept, a transmembrane activator and cyclophilin ligand interactor (TACI) fusion protein targeting B cell activating factor and a proliferation-inducing ligand (APRIL), has proven efficacy in treating Immunoglobulin A (IgA) nephropathy (IgAN). However, serum biomarkers that could predict the clinical response during the treatment remain unclear. Methods: Plasma samples from 24 participants in the phase 2 clinical trial were collected at baseline and after 4, 12, and 24 weeks; with 8 participants in the placebo group, 9 in the 160 mg group, and 7 in the 240 mg group. We measured the levels of galactose-deficient-IgA1 (Gd-IgA1), IgA-containing immune complexes, C3a, C5a, and sC5b-9. The association between the changes in these markers and proteinuria reduction was analyzed. Results: After 24 weeks of treatment, Gd-IgA1 decreased by 43.9% (95% confidence interval: 29.8%, 55.1%), IgG-IgA immune complex by 31.7% (14.4%, 45.5%), and poly-IgA immune complex by 41.3% (6.5%, 63.1%) in the 160 mg group; Gd-IgA1 decreased by 50.4% (38.6%, 59.9%), IgG-IgA immune complex decreased by 42.7% (29.5%, 53.4%), and poly-IgA immune complex decreased by 67.2% (48.5%,79.1%) in the 240 mg group. There were no significant changes in the circulatory C3a, C5a, or sC5b-9 levels during telitacicept treatment. Decreases in both plasma Gd-IgA1 and IgG-IgA or poly-IgA immune complexes were associated with proteinuria reduction. In turn, IgG-IgA or poly-IgA immune complexes showed a dose-dependent effect, consistent with proteinuria reduction during telitacicept treatment. Conclusion: Telitacicept lowered both circulating Gd-IgA1 and IgA-containing immune complexes, whereas IgA immune complex levels were more consistent with decreased proteinuria.